Effectiveness of quality physical education in improving students' manipulative skill competency - Weiyun Chen; Weimo Zhu; Steve Mason; Austin Hammond-Bennett; Andrew Colombo-Dougovito (Elsevier, 2016)
Purpose: This study aimed to examine the extent to which the quality physical education teaching (QPET) practices contributed to improving 4th- and 5th-grade students' manipulative skill competency. Methods: Participants were 9 elementary physical education (PE) teachers and their 4th- and 5th-grade students (n = 2709-3420). The students' skill competency was assessed with 3 manipulative skills using PE metrics assessment rubrics. The PE teachers' levels of QPET were assessed by coding 63 videotaped lessons using the assessing quality teaching rubrics (AQTR), which consisted of 4 essential dimensions including task design, task presentation, class management, and instructional guidance. Codes were confirmed through inter-rater reliability (82.4%, 84.5%, and 94%). Data were analyzed through descriptive statistics, multiple R2 regression models, and independent sample t tests. Results: This study indicated that the 4 essential dimensions of QPET were all significant contributors to students' manipulative skill competency. These predictors were significantly higher for boys than for girls in soccer and striking skills, while they were significantly higher for girls than for boys in throwing skill competency. Of the 4 essential dimensions of QPET, task presentation played the most significant role in contributing to all 3 skill competencies for both boys and girls. Further, students who experienced high QPET were significantly more skillfully competent than those students who did not have this experience. Conclusion: It was concluded that the QPET practices played a significantly critical role in contributing to students' manipulative skill competency.